Tongue-palate contact patterns for Croatian alveolar fricatives - Liker, Marko; Mildner, Vesna; Horga, Damir (2010)
Characteristics of tongue-palate contacts are necessary for a complete physiological description of speech sounds. Electropaltographic specification of alveolar fricatives in Croatian is aimed at providing speech therapists with normative data about the range of acceptable productions of /s/ and /z/ in adult speaker of Croatinan. Results show that Croatian /s/ and /z/ are alveolar and not dental as previously reported. Also, /s/ and /z/ are articulated with a high degree of tongue-palate contact symmetry. The comparison between the voiced and the voiceless counterpart being significantly longer. The difference between voiced and voiceless is also found in the total contact, with /z/ having more contact in the anterior four rows of electrodes, while /s/ having more contact in the posterior four rows of electrodes. Normal variability for each variable is quantified.
Projekt MZOS
Projekt MZOS
ENG